La visite au zoo et l’apprentissage de la distinction humaine - Véronique Servais (Revue d'anthropologie des connaissances)
The zoo might be regarded as a cultural device that structures the relationships between human beings and captive animals. In this study we searched to identify the patterns that connect visitors and captive animals during the zoo visit experience. We recorded and analysed the speech and interactions of visitors in front of the cages of two primate species: Orangutans (Pongo pygmaeus) and braza monkeys (Cercopithecus neglectus) with the aim of understanding how the human/non human boundary is practically accomplished.